Understanding Forest Tourism Business Marketing in the Perspective of Governance and Nature Protection - Rully Novie Wurarah; Jufri Jacob; Suslinawati Suslinawati; Naiyun Untung Utama; Yuli Purbaningsih (Enrichment : Journal of Management, 2022)
This study was conducted to answer the problem of marketing the forest business from a nature protection perspective following the government's commitment. Various efforts were made to promote tourism but maintain environmental balance, especially forest tourism—protection of nature and marketing of businesses and forests in various regions. Our search was done electronically, and we discussed efforts to find understanding under the phenomenological approach, where we want to answer a well-known problem from all the available data. After the discussion that was then, we could be concluded, among other things, that the marketing of eco-based tourism business is a commitment of all countries where on the one hand, the country wants to earn income to advance the country, on the other hand, it must also consider the protection of nature following the weakness of the command where forest It must be profitable as well as sustainable for the next generation. Thus, these findings should get meaningful input.